The CUNY Young Adult Program - Utilizing Social Networking to Foster Interdisciplinary and Cross-Cohort Student Communication during Workforce Training - Levine, Alissa; Winkler, Christoph; Petersen, Saul (Online Learning, 2010)
The Center for Economic and Workforce Development (CEWD) at Kingsborough Community College is currently working on a workforce development project that contains innovative teaching tools that proved successful in overcoming issues of academic isolation